(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cooling towers are one in every of the most necessary industrial utilities used to dissipate the unwanted method heat to the atmosphere through the cooling water within the heat exchangers across the plant site. Cooling system is one in every of the most expensive utility in terms of power consumption and water circulation. Maintaining water quality within the circulation loops is one in every of the main challenges in method improvement for many efficient performance. To identify the key performance parameters with respect to perspective of the operations’ team, the water chemistry is the most crucial level and demands proper understanding to maintain complete control over the variations.